Examining the combined effect of antenatal care visits and iron-folic acid supplementation on low birth weight: a pooled analysis of two national data sets from Nepal - Vishnu Khanal; Sangita Bista; Andy H. Lee (BMC, 2024)
Abstract Background The prevalence of low birth weight (LBW) has stagnated at approximately 12% for the past 15 years in Nepal, significantly impacting newborn survival. While antenatal care (ANC) visits and iron-folic acid supplementation are recognised as important interventions to reduce LBW, there is a lack of evidence regarding their combined effect. This study aimed to explore the potential synergistic impact of ANC and iron-folic acid supplementation on LBW in Nepal by analyzing data from two national surveys. Methods The nationally representative Nepal Demographic and Health Surveys of 2016 and 2022 were used, and the pooled dataset was analysed. Birth weight and the prevalence of LBW (i.e. birthweight < 2500 g) were reported using descriptive statistics. The associations among LBW, ANC visits, and iron-folic acid supplementation were examined using logistic regression analyses. Results The mean birth weight was 3011 g, with an LBW prevalence of 11.2%. Not attending ANC (Adjusted Odds Ratio (AOR): 1.49; 95% Confidence Interval (CI): 1.14, 1.95) and not consuming iron-folic acid supplements (AOR: 1.43; 95% CI: 1.11, 1.84) were independently associated with a higher likelihood of having LBW. Furthermore, when considering both factors together, mothers who attended less than four ANC visits and consumed iron-folic acid for ≤ 90 days had the higher likelihood of having LBW (AOR: 1.99; 95% CI: 1.35, 2.60) compared to those who did not. Conclusions This study highlights that the individual and joint influence of ANC visits and iron-folic acid supplementation on having LBW. These findings underscore the significance of ANC attendance and iron-folic acid supplementation in preventing LBW. Traditionally, these two interventions were primarily considered as maternal survival strategies. However, our findings indicate that these existing interventions could be utilised further for both maternal and newborn survival. Given that these services are offered free of cost and are available near people's homes through the National Safe Motherhood Programme in Nepal, efforts to increase the uptake of these services should be strengthened while emphasising their role in preventing LBW.